Analisis Wacana pada Akun Twitter @DivHumas_Polri dalam Manajemen Krisis Tragedi Kanjuruhan - Putri, Wahyu; Afrilia , Ascharisa Mettasatya; Istiyanto, Bekti; Hermawan, Rizal Rizky (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2024)
Polri as a law enforcement agency has a role as a community protection agency and should have a positive reputation in society. However, the fact is that Polri's reputation has suffered a significant decline after the Kanjuruhan tragedy. A number of public opinions, especially on social media, ultimately cornered the Police so that it had a negative impact on the existence of the Police's reputation. Police Public Relations utilizes Twitter social media to restore reputation after the Kanjuruhan tragedy. This study aims to analyze the discourse developed by Polri Public Relations as a crisis management strategy. This research is a descriptive study using qualitative methods and using the theoretical approach of critical discourse analysis proposed by Van Dijk. The results of the study show that the public relations discourse of the National Police through Twitter social media shows an image restoration strategy of denying it by blaming other parties. This is reflected in the text which focuses on describing the parties involved as the trigger for the Kanjuruhan tragedy. Accuracy in choosing a strategy can strengthen organizational attitudes and be able to change public opinion from negative and antipathy to positive and sympathy.